Wavelet-based damage localization and severity estimation of experimental RC beams subjected to gradual static bending tests. (December 2021) - Jahangir, Hashem; Hasani, Hamed; Esfahani, Mohammad Reza
Graphical abstract: Highlights: Damage detection of RC beams conducted by entropy-based wavelet transform. Both experimental and numerical RC beams in different damage levels were studied. Shannon entropy, normalizing and threshold implemented in obtaining damage index. Proposed damage index performs well in damage localization and severity estimation. The predicted crack propagation was consistent with experimental observations. Abstract: In this paper, the modal curvatures of experimental and numerical reinforced concrete (RC) beams were analyzed by wavelet transform to find the locations and severities of damages. Two RC beam specimens were selected from previous research works that were gradually damaged under four-point static bending tests, and following each loading step, modal tests were performed to achieve their dynamic parameters. Then, based on the selected experimental RC beams, numerical models including single, double and triple damage scenarios, as slots at different locations with constant width and different depths, were simulated to propose proper damage indices. By utilizing Shannon entropy, normalizing and applying threshold on the resulted wavelet coefficient of modal curvatures at undamaged and damaged states, two damage indices were proposed, in which one of them uses just the damaged modal data to conduct damage localization whereas the second one needs both damaged and undamaged modal data to estimate damage severities as long as damage locations. The results show that the second proposed damage index has the ability to assess the increasing trend of damage in different levels in addition to correctly detection the locations of all damage scenarios in numerical models. Moreover, regarding the experimental RC beams, the second proposed damage index could successfully detect the damaged degree of freedoms and the corresponding severities at different loading steps in both specimens. The predicted crack propagation trend by the proposed damage indices were consistence with the experimental observations.